Validation of the 6 MV TrueBeam linear accelerator model for out-of-field radiation dose calculation using PHITS Monte Carlo code - Suwanbut, Pattarakan; Liamsuwan, Thiansin; Nantajit, Danupon; Masa-nga, Wilai; Tannanonta, Chirapha (Journal of Associated Medical Sciences, 2021)
Background: Radiotherapy treatment planning usually concerns in-field radiation dose to produce a high therapeutic ratio with high dose to the target and minimum normal tissue complication. However, out-of-field radiation dose should also be considered because it causes additional radiation exposure to the patient, resulting in an increased risk for developing secondary cancer in the patient and health consequences in the fetus if the patient is pregnant. Monte Carlo simulation is useful for estimating out-of-field dose. The American Association of Physicists in Medicine Task Group 158 (AAPM TG 158) recommends that Monte Carlo simulation for calculation of out-of-field radiation dose should be validated in terms of percentage depth dose, lateral beam profile, dose near the phantom surface and peripheral dose. Objectives: To validate the 6 MV TrueBeam linear accelerator model developed using Particle and Heavy Ion Transport code System (PHITS) Monte Carlo code for out-of-field dose calculation for the field sizes of 10x10, 10x20 and 40x40 cm2. Materials and methods: The Monte Carlo simulation was validated against experimental data at the same conditions. Percentage depth dose, lateral beam profile and dose near the phantom surface were measured at 10x10, 10x20, and 40x40 cm2 field sizes, while peripheral doses were measured using 10x10 cm2 field size at 0, 5, 10 and 15 cm distances from the field edge and at 5 and 10 cm depths in a water phantom. The 6 MV radiation fields were delivered using Varian TrueBeam linear accelerator. For the Monte Carlo simulation, phase space data above the jaws were provided by the vendor. PHITS code version 3.20 was used for modeling the treatment head downstream of the phase space surface and the measurement set-up. The gamma evaluation method was used to compare between the calculation and the measurement. Results: The experimental data and the Monte Carlo simulation were in good agreement. The gamma passing rates with 3%/3mm criteria were 100% for percentage depth dose, 95% for lateral beam profile, 50% for dose near the phantom surface and 81% for peripheral dose. Conclusion: The 6 MV TrueBeam linear accelerator model developed using PHITS Monte Carlo code was validated according to the AAPM TG 158’s recommendation. The simulation results showed good agreement with the experimental data. Therefore, this Monte Carlo model can be used for out-of-field dose calculation.